Impact of expanding indications on surgical and oncological outcome in 1434 consecutive pancreatoduodenectomies. Issue 7 (July 2019) - van Roessel, Stijn; Mackay, Tara M.; Tol, Johanna A.M.G.; van Delden, Otto M.; van Lienden, Krijn P.; Nio, Chung Y.; Phoa, Saffire S.K.S.; Fockens, Paul; van Hooft, Jeanin E.; Verheij, Joanne; Wilmink, Johanna W.; van Gulik, Thomas M.; et al.
Abstract: Background: Over the years, high-volume pancreatic centers expanded their indications for pancreatoduodenectomy (PD) but with unknown impact on surgical and oncological outcome. Methods: All consecutive PDs performed between 1992–2017 in a single pancreatic center were identified from a prospectively maintained database and analyzed according to three time periods. Results: In total, 1434 patients underwent PD. Over time, more elderly patients underwent PD (P < 0.001) with increased use of vascular resection (10.4 to 16.0%, P < 0.001). In patients with cancer (n = 1049, 74.8%), the proportion pT3/T4 tumors increased from 54.3% to 70.6% over time (P < 0.001). The postoperative pancreatic fistula (16.0%), postpancreatectomy hemorrhage (8.0%) and delayed gastric emptying (31.0%) rate did not reduce over time, whereas median length of stay decreased from 16 to 12 days (P < 0.001). The overall failure-to-rescue rate (6.9%) and in-hospital mortality (2.2%) remained stable (P = 0.89 and P = 0.45). In 523 patients with pancreatic cancer (36.5%), the use of both adjuvant and neoadjuvant chemotherapy increased over time (both p<0.001), and the five-year overall survival improved from 11.0% to 17.4% (P < 0.001). Conclusions: In a period where indications for PD expanded, with more elderly patients, more advanced cancers and increased use of vascular resections, surgical outcome remained favorable and five-year survival for pancreatic cancer improved.